Fundamentals of computer networks: wired/wireless - Abubakar, Adamu; Zeki, Akram M. (IIUM Press, 2015)
This chapter introduces the concept of computer network. The tools, resources and standards of computer network have also being represented. The major component of computer network is people on the network and those managing the network; as a result the chapter highlights their interrelationships under different scheme. There is an interleaving space between a computer network and data network, which they seem to mean the same in terms of network system which allows computers to exchange data. Although, in computer networks the hardware or networked computing devices are the major subject matter, which are operating by the network management group, while the data which the users generate and put into the network to be send to other locations through the networking device are also consider to be part of the network. In this case, multiple computers and other computing devices connected together share information in an interconnected group of computers and communication devices, thus a network consists of 2 or more computing device connected together and share resources. Therefore, the terminology “Network” in computing are classify in to four namely; network by size, network by transmission medium, network by arrangement or topology, and finally network by management strategies. This chapter highlights the different types of network and the networking devices and the standard or protocol which the network operates.